The detection of cytomegalovirus DNA in maternal plasma is associated with mortality in HIV-1-infected women and their infants. - Slyker, J; Lohman-Payne, B; Rowland-Jones, S; Otieno, P; Maleche-Obimbo, E; Richardson, B; Farquhar, C; Mbori-Ngacha, D; Emery, VC; John-Stewart, G (2009)
OBJECTIVE: Cytomegalovirus (CMV) is an important pathogen in healthy neonates and individuals with human immunodeficiency virus (HIV-1). The objective of this study was to determine whether the detection of CMV DNA (CMV DNAemia) in maternal plasma was associated with mortality in HIV-1-infected women or their infants. METHODS: A longitudinal study was designed to examine the relationship between maternal CMV DNAemia and maternal-infant mortality during 2 years postpartum. Sixty-four HIV-1-infected women and their infants were studied. CMV DNA loads were quantified in plasma from the mothers near the time of delivery. Baseline maternal CD4 cell counts, CD4%, HIV-1 RNA, and CMV DNAemia were evaluated as covariates of subsequent maternal or infant mortality in univariate and multivariate Cox regression. RESULTS: CMV DNA was detected in 11/64 (17%) of the HIV-1-infected women. HIV-1 and CMV viral load were strongly correlated in CMV DNAemic women (rho = 0.84, P = 0.001). Detection of CMV DNAemia was associated with decreased maternal survival at 24 months postpartum (log-rank P = 0.006). Additionally, HIV-1-infected infants born to CMV DNAemic women had a four-fold increased risk of mortality during 24 months of follow-up. Maternal CMV DNAemia remained a significant risk factor for mortality in HIV-1-infected infants after adjusting for maternal CD4 cells/microl [adjusted hazard ratio (HR) = 4.3, confidence interval (CI) = 1.4-13], CD4% (HR = 3.2, CI = 1.0-10), HIV-1 viral load (HR = 4.1, CI = 1.4-12) or maternal death (HR = 3.7, CI = 1.0-13). CONCLUSION: Maternal plasma CMV DNAemia identified a subgroup of Kenyan women and infants at high risk for death in the 2 years following delivery.